In vitro evaluation of force degradation of elastomeric chains used in Orthodontics - André Weissheimer; Arno Locks; Luciane Macedo de Menezes; Adriano Ferreti Borgatto; Carla D'Agostini Derech (Dental Press Editora, 2013)
OBJECTIVE: To analyze the in vitro force degradation of four different brands of elastomeric chains: American Orthodontics, Morelli, Ormco and TP Orthodontics. METHODS: The sample consisted of 80 gray elastomeric chains that were divided into four groups according to their respective manufacturers. Chain stretching was standardized at 21 mm with initial force release ranging from 300 g to 370 g. The samples were kept in artificial saliva at a constant temperature of 37°C and the degradation force was recorded at the following time intervals: initial, 1, 3, 5, 7 and 9 hours, and 1, 7, 14, 21, 28, and 35 days. RESULTS: There was a statistically significant difference between the groups regarding the force degradation, mainly within the first day, as a force loss of 50-55% was observed during that time in relation to the initial force. The force delivered at 35 days ranged from 122 g to 148 g. CONCLUSION: All groups showed force degradation over time, regardless of their trademarks, a force loss of 59-69% was observed in the first hour compared to baseline. However, because the variation in force degradation depends on the trademark, studies such as the present one are important for guiding the clinical use of these materials. OBJETIVO: analisar, in vitro, a degradação de força, ao longo do tempo, de elastômeros das marcas comerciais American Orthodontics, Morelli, Ormco e TP Orthodontics. MÉTODOS: a amostra constituiu-se de 80 segmentos de elastômeros em cadeia fechada na cor cinza, divididos em quatro grupos, conforme o fabricante. A distensão foi padronizada em 21mm, com liberação de força inicial variando de 300 a 370g de força. As amostras foram mantidas em saliva artificial em temperatura constante de 37ºC, e a força avaliada nos seguintes intervalos: inicial, 1h, 3h, 5h, 7h, 9h, 1 dia, 7 dias, 14 dias, 21 dias, 28 dias e 35 dias. RESULTADOS: houve diferença estatisticamente significativa na degradação de força entre os grupos avaliados, sendo que no primeiro dia houve perda de 50 a 55% em relação à força inicial. Os valores médios de força em 35 dias variaram de 122 a 148g. CONCLUSÃO: todas as marcas comerciais apresentaram degradação de força ao longo do tempo, sendo que na primeira hora a perda de força esteve entre 59 e 69% da força inicial. Porém, como existe variação dessa degradação dependendo da marca comercial, estudos como esses são importantes para orientação do uso desses elastômeros.